Earth greening and climate change reshaping the patterns of terrestrial water sinks and sources - Yu Yan; Zhiyong Liu; Lei Chen; Xiaohong Chen; Kairong Lin; Zhenzhong Zeng; Xin Lan; Liyan Huang; Yajun Wang; Lili Yao; Linyin Cheng; Zhimin Ma (Proceedings of the National Academy of Sciences, 2025)
While vegetation brings positive benefits for climate mitigation and adaptation, the impact of ongoing global greening remains controversial due to its uncertain effects on hydrological cycle. Here, we quantitatively assess the impact of vegetation dynamics on global water availability by proposing a comprehensive framework to quantify the terrestrial water sink and source scores associated with vegetation dynamics. These scores serve as indicators of whether large alterations in water resources have occurred in the lands due to either the greening or degradation of surface vegetation. We use multisource datasets from climate model projections, remote sensing, and local measurements to examine the impact of vegetation dynamics on water availability over the periods of 1982 to 2019 and 2015 to 2100. During historical observation periods, regions such as India and northern China experienced large depletion of water resources as a result of vegetation greening, leading to water scarcity. In the future, a shift is projected for India and northern China, transforming them into regions capable of meeting water demands arising from vegetation greening. This transition is largely attributed to wetting and warming climates. It indicates that trade-off effects between climate and underlying vegetation dynamics may result in strengthening regional hydrological resilience and ensuring the stable status of local water resources. Furthermore, tropical rainforests (except for the Amazon Rainforest) are experiencing greening with minimal impact on local water resources consistently. These insights are valuable for globally identifying optimal locations to implement ecological restoration, facilitating the balance of sustainable water resources and vegetation greening.